2012
DOI: 10.1021/jp304221z
|View full text |Cite
|
Sign up to set email alerts
|

Electrochromism of LixFePO4 Induced by Intervalence Charge Transfer Transition

Abstract: The lithium-ion battery is the most advanced energy storage system, which utilizes an electrode reaction involving reversible lithium intercalation into a solid matrix. The structural and transport properties of these battery materials have been extensively studied as a function of lithium content, and structural/electronic phase diagrams have been revealed for a wide variety of lithium intercalation compounds. Here, we focused on the electrochromic response upon lithium intercalation and discovered distincti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(66 citation statements)
references
References 35 publications
9
57
0
Order By: Relevance
“…These results agree with various previouss tudies for the two-phase reaction in LFP/FP under a thermodynamic equilibrium condition, [1,2] whereas a metastable phase was found by some experiments and theoretical analyses. [15][16][17] In addition, the present XES results for a that is electrochemically delithiated FP are similar to previousF eL 3edge resonant XES spectra for chemically delithiated( oxidized) FP reported by Augustsson et al [11] Hereafter,w ec oncentrate the Fe T his is consistentw ith that the satellite structure C in the L 3 -edge XAS reflects CT effects from the O2p to Fe 3d orbitals.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…These results agree with various previouss tudies for the two-phase reaction in LFP/FP under a thermodynamic equilibrium condition, [1,2] whereas a metastable phase was found by some experiments and theoretical analyses. [15][16][17] In addition, the present XES results for a that is electrochemically delithiated FP are similar to previousF eL 3edge resonant XES spectra for chemically delithiated( oxidized) FP reported by Augustsson et al [11] Hereafter,w ec oncentrate the Fe T his is consistentw ith that the satellite structure C in the L 3 -edge XAS reflects CT effects from the O2p to Fe 3d orbitals.…”
Section: Resultssupporting
confidence: 89%
“…The XES spectra for the intermediate states in the 3.45 V plateau, for example, sample c (80 mAhg −1 discharge), were reproduced by the superposition of a and e (Figure S2 f), indicating a simple two‐phase reaction consisting of FP and LFP components. These results agree with various previous studies for the two‐phase reaction in LFP/FP under a thermodynamic equilibrium condition, whereas a meta ‐stable phase was found by some experiments and theoretical analyses . In addition, the present XES results for a that is electrochemically delithiated FP are similar to previous Fe L 3 ‐edge resonant XES spectra for chemically delithiated (oxidized) FP reported by Augustsson et al…”
Section: Resultsmentioning
confidence: 99%
“…Because their sample heat‐treatments were performed over time, and the equilibrium was likely approached, the reported experimental data of Dodd et al is considered to be more reliable and should be utilized to verify any models of FePO 4 ‐LiFePO 4 olivine join. Interestingly enough, the XRD (x‐ray diffraction) and SAED (selected area electron diffraction) patterns of the Li 0.6 FePO 4 sample annealed at 623.15 K, confirming the existence of a supercell microstructure corresponding to long‐range‐order (LRO) . Furutsuki et al then proposed short‐range‐order (SRO) distribution of Li + and Va 0 only within a supercell.…”
Section: Literature Reviewmentioning
confidence: 89%
“…This quenched phase remained stable for a couple of weeks, which enabled sufficient time to measure the several intrinsic properties. [19][20][21] The structural analysis of metastable Li 2/3 FePO 4 (see Fig. 10a) revealed that the charge-ordered stripes at the Fe sites and the disordered configuration of lithium resulted from the electrostatic frustrations among the lithium and Fe 3+ ions.…”
Section: Metastable Intermediate: Structure Transport and Opticalmentioning
confidence: 99%
“…Inclusion of Fe 3+ /Fe 2+ mixed valence state modify the electronic density of state to induce optical absorption caused by inter-valance charge transfer transition, leading to a deeper color of the sample powder. 19 …”
Section: Metastable Intermediate: Structure Transport and Opticalmentioning
confidence: 99%